Effects and Mechanisms of Tea for the Prevention and Management of Diabetes Mellitus and Diabetic Complications: An Updated Review - Jin-Ming Meng; Shi-Yu Cao; Xin-Lin Wei; Ren-You Gan; Yuan-Feng Wang; Shu-Xian Cai; Xiao-Yu Xu; Pang-Zhen Zhang; Hua-Bin Li (MDPI AG, 2019)
Diabetes mellitus has become a serious and growing public health concern. It has high morbidity and mortality because of its complications, such as diabetic nephropathy, diabetic cardiovascular complication, diabetic neuropathy, diabetic retinopathy, and diabetic hepatopathy. Epidemiological studies revealed that the consumption of tea was inversely associated with the risk of diabetes mellitus and its complications. Experimental studies demonstrated that tea had protective effects against diabetes mellitus and its complications via several possible mechanisms, including enhancing insulin action, ameliorating insulin resistance, activating insulin signaling pathway, protecting islet β-cells, scavenging free radicals, and decreasing inflammation. Moreover, clinical trials also confirmed that tea intervention is effective in patients with diabetes mellitus and its complications. Therefore, in order to highlight the importance of tea in the prevention and management of diabetes mellitus and its complications, this article summarizes and discusses the effects of tea against diabetes mellitus and its complications based on the findings from epidemiological, experimental, and clinical studies, with the special attention paid to the mechanisms of action.